Episodic Lithospheric Deformation in Eastern Tibet Inferred From Seismic Anisotropy. Issue 3 (3rd February 2020) - Bao, Xuewei; Song, Xiaodong; Eaton, David W.; Xu, Yixian; Chen, Hanlin
Abstract: Mechanisms for uplift and deformation of the Tibetan Plateau remain vigorously debated; hypotheses include stepwise growth, distributed thickening, and crustal channel flow, each with a distinct anisotropic signature. We have developed a new azimuthally anisotropic shear velocity model for the lithosphere beneath eastern Tibet, based on ambient noise tomography from 643 seismic stations. In our model, the Tibetan upper crust is characterized by strong anisotropy with fast axes that correlate with surface geology and mantle anisotropy, suggesting the occurrence of coherent deformation. However, a much different picture emerges in the middle and lower crust, where anisotropy is disordered and weaker beneath the plateau than along its margins, inconsistent with the prediction of large‐scale eastward crust flow in eastern Tibet. Our observations are best explained by heterogeneous crustal thickening beneath the plateau with complex flow in the middle and lower crust, accompanied by asthenospheric upwelling along the southeastern plateau margin. Plain Language Summary: How the Tibetan Plateau uplifted and deformed remains debated. An azimuthally anisotropic shear velocity model beneath eastern Tibet was constructed to constrain its deformation style. The anisotropy of Tibetan upper crust displays continuously varying intensities and fast directions correlating well with surface geology and mantle anisotropy, confirming the occurrence of distributed coherent lithospheric deformation. Interestingly, middle‐lower crustal anisotropy is much weaker beneath the plateau proper than the northeastern and southeastern plateau margins, inconsistent with the prediction of large‐scale eastward crustal flow. Based on our observations and previous studies, we propose an episodic growth model for the plateau, in which heterogeneous crustal thickening was a primary driver at the early stage and the weakened middle‐lower crust flowed locally at a later stage without consistent directions. The southeastern plateau margin was raised likely by an additional mechanism of asthenospheric upwelling. Key Points: We construct a high‐resolution azimuthally anisotropic Vsv model for eastern Tibet and its surroundings An episodic deformation model with early crustal thickening and later disordered crustal flow was proposed for the plateau The SE plateau margin was likely uplifted by asthenospheric upwelling